Formalizm działania administracji publicznej jako niedoskonała pochodna zasady praworządności - Niżnik-Dobosz, Iwona (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In prism of relation to law of public administration as a subject executing law, referring to A. Błaś’s stances, the author represents requirements and implications of legal regulation of discretion in public administration operation. Subsequently she moves to a notion of law as an instrument formalising law subjects’ behaviour and to public administration formalism understood as a discrepancy in this operation (product of operation) between a principle and a rule; a wording and a spirit of law; hence as an invariable and eternal problem of organising, synchronising relations between lex and ius.
Keywords: formalism of public administration operation; formality and formalisation of legal norms